2018
DOI: 10.1142/s0218863518500182
|View full text |Cite
|
Sign up to set email alerts
|

Bonding state energy of metal nanoparticle dimer and its dependence on nanosphere size and interparticle separation

Abstract: A study is conducted regarding the effects of particle size [Formula: see text] and interparticle separation [Formula: see text] on the electromagnetic (plasmon) coupling in a dimer of two identical metal nanospheres. The dimer states are modeled as the hybridized bonding and antibonding states of two isolated plasmon states, with the associated energies given in terms of the isolated plasmon energy ([Formula: see text], the coupling energy ([Formula: see text] and the overlap integral ([Formula: see text] of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Company size is one of the important variables in company management. Company size reflects how big the total assets owned by the company (Octavus & Adiputra, 2020;Stephanie et al, 2018). A larger company size will attract the attention of the public, so that a large company will be more careful in carrying out earnings management.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Company size is one of the important variables in company management. Company size reflects how big the total assets owned by the company (Octavus & Adiputra, 2020;Stephanie et al, 2018). A larger company size will attract the attention of the public, so that a large company will be more careful in carrying out earnings management.…”
Section: Discussionmentioning
confidence: 99%
“…By having large assets, the company will earn a large income as as (Makhdalena, 2018). Several previous researchers conducted by Makhdalena (2018); Stephanie et al, (2018), concluded that firm size had an effect on strong financial performance. ultimately can affect the company's performance.…”
Section: Discussionmentioning
confidence: 99%